2014
DOI: 10.1016/j.ygyno.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Physician pain and discomfort during minimally invasive gynecologic cancer surgery

Abstract: Objective Despite increasing awareness of physical strain to surgeons associated with minimally invasive surgery (MIS), its use continues to expand. We sought to gather information from gynecologic oncologists regarding physical discomfort due to MIS. Methods Anonymous surveys were e-mailed to 1,279 Society of Gynecologic Oncology (SGO) members. Physical symptoms (numbness, pain, stiffness, and fatigue) and surgical and demographic factors were assessed. Univariate and multivariate analyses were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 19 publications
1
51
0
1
Order By: Relevance
“…Since its introduction robotic technology has been reported to have greater benefits for surgeons' musculoskeletal health as compared to SS [21,22], although it is not without ergonomics issues typically from fixed position at the console [19,23], compared to SS [24], which instead has a greater impact on shoulder and arm movement [25]. Newer robotic platforms are currently under development that have worked on this aspect with open consoles that will hopefully help address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction robotic technology has been reported to have greater benefits for surgeons' musculoskeletal health as compared to SS [21,22], although it is not without ergonomics issues typically from fixed position at the console [19,23], compared to SS [24], which instead has a greater impact on shoulder and arm movement [25]. Newer robotic platforms are currently under development that have worked on this aspect with open consoles that will hopefully help address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not differentiate the physical strains caused by robotic surgery or laparoscopic surgery. McDonald et al [ 23 ] completed a similar ergonomic survey study for comparing the physical ergonomics of robotic, laparoscopic, or abdominal surgery. They reported that physical symptom rate of the robotic surgery group was higher (72%) than those of laparoscopic (57%) and abdominal surgery group (49%).…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, the only study evaluating surgeon pain in gynecologic oncology did not support improved ergonomics for surgeons with the robotic system: in fact, gynecologic oncologists reported increased pain with use of the robotic system. 26 Several studies have shown that TL is more cost-effective than RAS and open laparotomy for the treatment of endometrial cancer. 27,28 Barnett et al showed that laparoscopic hysterectomy was associated with an average cost savings of $1347 compared to robotic-assisted hysterectomy and $2719 compared to open hysterectomy.…”
Section: Discussionmentioning
confidence: 99%